Experimental study on motion response of a submersible spherical model under the action of internal solitary wave propagating over a ridge topography. (15th August 2022) - Cui, Junnan; Dong, Sheng; Wang, Zhifeng; Cheng, Junyu; Ren, Jiayin
Abstract: Experimental investigations are performed to study the motion response of submerged spherical model under internal solitary waves propagating over a ridge topography. This study is based on our previous work, that revealed the motion responses of submerged models under internal solitary waves. The relative initial depth between the model and pycnocline, size of topography and upstream/downstream effect of the topography are considered. The velocity and vorticity of fluid are analyzed following particle image velocimetry (PIV) method, and the motion response of the spherical model is analyzed by using image processing algorithms. The results show that the maximum heave motion amplitude and the maximum surge motion amplitude of the model increases 1.9 times and 2.2 times due to the influence of topography, respectively. The heave motion of model in the downstream direction of the topography is twice as much as that in the upstream direction. The flow field becomes extremely complex near the topography resulting in more intense motion response of the submerged model with maximum heave motion amplitude greater than 1.8 times of amplitude of the incident wave. Therefore, internal solitary waves that propagate over ridge topography could pose a significant threat to submersible structure. Highlights: Motion response of model under ISW propagating over topography is studied experimentally. Image process method is used to analyze interface displacement and model motion response. Presence of topography increases heave amplitude of submersible model. Model in upstream direction of topography experience more intense motion response. Size of the topography has a significant influence on motion response.